Legal Aspects of Zakat Empowerment In Indonesia - Sofyan Hasan; Taroman Pasyah (Sriwijaya Law Review, 2019)
Zakat is a number of certain assets that the Muslim people have to give to the persons who are in need. However there are some problems in the zakat management in Indonesia. The objective of this article is to provide for a brief picture of the zakat management in Indonesia. The findings of the research conducted that it was found in 2011 that the Zakat agencies have been able to manage up to ten billion rupiahs which distribution covers the whole parts of Indonesia. Nevertheless, in Indonesia zakat has a big potential, by having 87% of Muslim populations and 20% of them are assumed as the zakat givers (muzakki). Therefore as it was reported in 2011 that the potential value of zakat was around Rp 217 trillions. In addition, the zakat added with infaq calculated around Rp 1.5 trillion per year. Meaning that the zakat collected has not reached even more than 1 percent of the potential zakat per year. Even though the number of Muslim people in Indonesia is very significant, the problems centered in the management of the zakat which is still in traditional pattern where the zakat givers (muzakki) give directly to the persons who has the right to receive zakat (mustahik). It is suggested that it need revolutionary improvement in the zakat management, there must be a mindset changing from traditional management to modern zakat management where the zakat officer (amil zakat) must be a professional one, and permanent job basis. This surely will improve the zakat management and the poverty will surely be eliminated. This research used empirical methods including the effectiveness and impact of the law